Reduction of pH by homolactic fermentation as indicator of fecal coliform inactivation in wastewater - Alva-Araujo, Jean Poll (2021)
The purpose of this research was to evaluate the capability of lactic acid bacteria (LAB) to remove pathogens present in domestic wastewater, generated in the eco-touristic circuit Lomas de Lucumo (Lima, Peru). The pH decrease was used as an indicator of the elimination of fecal coliform bacteria in the treated water. Experiments included 36 treatments, which consisted of different mixtures of sugar molasses and a lactic acid bacteria inoculum (B-Lac) in proportions of 0, 1, 3, 5, 7 and 10% (v/v) and wastewater in a fixed proportion of 200 ml, under a completely randomized design (CRD) with factorial arrangement 6x6. The pH values on the third day were evaluated using an Analysis of Variance (ANOVA) followed by Tukey´s range test for mean differences (p < 0.05). The different treatments were analyzed in a first stage for 9 days, after which the best three were selected for a second evaluation: T16 (3% molasses and 5% B-Lac), T22 (5% molasses and 5% B-Lac) and T33 (10% molasses and 3% B-Lac); results show that the interaction effect between the two variables is significant. Finally, treatment T16 was selected as the most efficient, reaching a pH of 4.08 in a short time (3 days) that assured the complete removal of fecal coliform bacteria (9.65x105 MPN/100 ml) in the wastewater.